Testing the Vitamin B12 Levels in Cassava Tapai - Sanchia Cleosha Viorina; Septi Handayani; Nisa Kartika Komara; Nawan Nawan; Ina Arleny (International Journal of Health Engineering and Technology, 2026)
Anemia remains a major public health issue in Indonesia, including Central Kalimantan, and is often linked to vitamin B12 deficiency. Vitamin B12 is typically found in animal-based foods; However, certain microorganisms involved in the fermentation of plant-based foods, such as cassava tapai, can synthesize this vitamin. This study aims to determine the vitamin B12 content and its variation in cassava tapai from Palangka Raya City based on fermentation duration. A comparative descriptive study with a quantitative approach was conducted using 16 samples obtained through purposive sampling from four local tapai producers at Pasar Besar A. Yani, Palangka Raya. Vitamin B12 levels were measured using UV-Vis spectrophotometry at 361 nm, and organoleptic properties (color, aroma, taste, texture) were analyzed descriptively. The results showed that all samples contained vitamin B12 ranging from 453,736,666.67 to 1,588,180,000.00 mcg/100g, with levels increasing along with fermentation time (days 1–4). Organoleptic tests revealed non-white color, alcoholic aroma, slightly sweet to unsweet taste, and soft texture. In conclusion, cassava tapai produced by MSMEs in Palangka Raya contains high levels of vitamin B12 and holds promise as a potential local food source to help prevent vitamin B12 deficiency anemia